EVALUATION OF HONEY QUALITY: COMPARISON OF THE PHYSICO-CHEMICAL COMPOSITION INITIALLY AND AFTER TWO YEARS OF STORAGE - George MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study presents the evaluation of the quality of honey according to its physico-chemical composition, both at the time of harvesting and after two years of storage. Important parameters such as sugar content, moisture, pH, enzyme activity and other characteristics are measured and compared to determine whether and how storage influences these properties. The results of the study may provide valuable information for the beekeeping industry and consumers, highlighting the impact of long-term storage on honey quality and safety.